Uji aktivitas antibakteri fraksi n-heksana dan etil asetat daun bandotan (Ageratum conyzoides L.) terhadap bakteri Staphylococcus epidermidis - Rafliza , Rista; Nasution , Haris Munandar; Dalimunthe , Gabena Indrayani; Mambang , D.Elysa Putri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Bandotan (Ageratum conyzoides L) is a wild plant that is easy to find in Indonesia, known to have medicinal properties and has antibacterial properties. The purpose of this study was to determine the antibacterial activity of the n-hexane and ethyl acetate fractions of bandotan leaves (Ageratum Conyzoides L) against Staphylococcus epidermidis bacteria.This research was conducted using an experimental method including sample collection, macroscopic examination, microscopic examination, simplicia manufacture, characteristic examination, phytochemical screening, preparation of ethanol extract, then fractionation, then testing of antibacterial activity against Staphylococcus epidermidis bacteria using the agar diffusion method. Data obtained from the diameter of inhibition were statistically analyzed using the Anova test, then followed by the Kruskal-Wallis test and the Ducan test. The results of macroscopic examination, with dark color, egg-shaped, two pointed, obtuse leaf base, serrated leaf margins, hairy veins on the upper and lower surfaces, slightly hairy young leaves, white hair color and pinnate veins. The results of microscopic examination, xylem, covering hair, mesophyll and anomocytic type of stomata. The simplicia characteristic results obtained water content of 7.3%, water-soluble essence content of 32.72%, 42.5% ethanol-soluble extract content, total ash content of 3 .3% and acid insoluble ash content of 1.8%. Phytochemical screening of simplicia powders and extracts showed the presence of alkaloids, glycosides, flavonoids, tannins, saponins and steroids. The results of the antibacterial activity test of the n-hexan fraction on Staphylococcus Epidermidis bacteria at concentrations of 10%, 30%, 50% and 70% were included in the resistant category. Meanwhile, the ethyl acetate fraction at a concentration of 10%, 30% and 50% is in the resistant category, at a concentration of 70% it is in the intermediate category. So it can be concluded that the n-hexane and ethyl acetate fractions of bandotan leaves (Ageratum conyziodes L) have activity against Staphylococcus epidermidis bacteria..